TAQWÎM AL BARNĀMIJ AL MUKATSTSAF LITA’LÎM AL LUGHAH AL ’ARABIYYAH FÎ AL MADRASAH AL MUTAWASSITAH AL ISLĀMIYYAH AL HUKŪMIYYAH AL TSĀNIYAH KEDIRI - Akmalia, Frida; Syihabuddin, Syihabuddin (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2020)
Intensive Arabic Program is one of the activities to develop students knowledge in achieving learning objectives. Lack of time in the school activitiy is one of the reasons for lack of optimal learning in the school, especially in the learning Arabic which is considered a difficult foreign language for students. This research aims to explain the type of Arabic language extracurricular activities at MTsN 2 Kediri, the implementation, the evaluation of learning, and the obstacles encountered during the implementation. This research used a qualitative approach with interview, observation, and documentation. The results of this research indicate that the type of Intensive Arabic Program activities at MTsN 2 Kediri is the fostering of Arabic language achievement which focuses on speaking skills. The implementation of it’s activities at MTsN 2 every day and every years. Evaluation of learning by giving post-test, quizz, midterm, final examination, and on going activities. In its implementation the researcher found some obstacles, including activities that are less interesting. Keywords: Intensive Program, Arabic Language, Evaluation.